(untitled) (Andamios, Revista de Investigación Social, 2024)
The pedagogical character of Ignacio Ellacuría is a hermeneutics of the person and the character he represents according to his Christian and Jesuit vocation. Thus, it is an interpretation that identifies in the legacy of the Salvadoran Martyr a testimonial pedagogy, which is situated in the intellective, ethical and practical dimensions that identify him. By going through his formative trajectories, his intellective dynamism and the scope of his praxis, a pedagogical character is interpreted that is enunciated from his Christian work, the charge of his reality and his martyrdom. Hence, when considering the historical and mystagogical dimension that reality has for the Salvadoran Martyr, it is a character underlying his intellectual and biographical legacy, aspects that intuit a historical pedagogy whose pedagogical subject is a historicized intellectual.